2020
DOI: 10.1038/s41598-020-61057-4
|View full text |Cite
|
Sign up to set email alerts
|

The ankyrin repeat gene family in Capsicum spp: Genome-wide survey, characterization and gene expression profile

Abstract: the ankyrin (AnK) repeat protein family is largely distributed across plants and has been found to participate in multiple processes such as plant growth and development, hormone response, response to biotic and abiotic stresses. it is considered as one of the major markers of capsaicin content in pepper fruits. In this study, we performed a genome-wide identification and expression analysis of genes encoding AnK proteins in three Capsicum species: Capsicum baccatum, Capsicum annuum and Capsicum chinense. We i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 93 publications
(101 reference statements)
1
17
0
Order By: Relevance
“…The ankyrin repeat protein family participates in multiple processes, including response to biotic and abiotic stresses by activating downstream defense signaling components [35]. We found two highly upregulated transcripts (Ta.19805.2.S1_a_at and Ta.4670.1.A1_at) representing the ankyrin repeat family, which is in agreement with the known role of ANK genes in achieving resistance to biotic and abiotic stresses.…”
Section: Putative Genes With the Highest Differential Expression And Their Rolesupporting
confidence: 87%
“…The ankyrin repeat protein family participates in multiple processes, including response to biotic and abiotic stresses by activating downstream defense signaling components [35]. We found two highly upregulated transcripts (Ta.19805.2.S1_a_at and Ta.4670.1.A1_at) representing the ankyrin repeat family, which is in agreement with the known role of ANK genes in achieving resistance to biotic and abiotic stresses.…”
Section: Putative Genes With the Highest Differential Expression And Their Rolesupporting
confidence: 87%
“…In rice (Oryza sativa) and tomato (Solanum lycopersicum), 175 and 130 ANK genes have been identi ed and classi ed into 10 and 13 subfamilies respectively (Huang et al 2009;Yuan et al 2013). Recently, 87, 85 and 96 ANK genes have been reported in C. baccatum, C. annuum and C. chinense genomes, respectively (Lopez-Ortiz et al 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, Thieme et al [ 46 ] reported that the RNA polymerase II (Pol II) gene may be associated with stress. The A6147 marker is on the putative ankyrin repeat protein gene and the putative ankyrin repeat protein family is widely distributed among plants and has been found to participate in multiple processes, such as plant growth and development, hormone response, and response to biotic and abiotic stresses [ 47 ]. More importantly, this gene has been reported to be required for disease resistance [ 48 ], and it has been found that the markers we have identified are on same chromosomes previously identified by different researchers [ 49 ].…”
Section: Discussionmentioning
confidence: 99%